College physics with an integrated approach to forces and kinematics. Volume 2 - Giambattista, Alan (McGraw-Hill Higher Education, 2010)
Mechanics; Thermal physics; Electromagnetism; Electromagnetic waves and optics; Quantum and particle physics and relativity